Performance Analysis of Foreign Loans in Directorate General of Highways Ministry of Public Works - Yunik Eva Sarlina (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2016)
Provision of road infrastructure does, efficiently and effectively, have an effect on economy increase in a region. The limited ability of the government in the provision of funding for the road infrastructure requires the handling on the organizers of the roads, it also needs efforts to look for funding resources outside the APBN as a resource of funds for foreign loans. This study aims to know the process of foreign loans, the characteristics of each foreign loan, and the loan implementation performance in Directorate General of Highways, Ministry of Public Works. The research was using the qualitative descriptive methods focusing on thorough depiction of form, function, and meaning of prohibition; data collection was done by collecting the entire loan process from the preparation phase to the implementation phase through interviewing and documentation literature. The document consists of the loan agreement document, documents monthly reports and annual reports, lender regulations, legal regulations of the Republic of Indonesia, photo documentation and archives. The result showed that the scoring of performance, multilateral loan is better than bilateral loan. This is evidenced by higher score for multilateral loan than bilateral loan. Particularly in terms of regulations, the multilateral loan having score 15, it was because the lender adjusts by existing regulations in Indonesia, while bilateral loan having score 13. Furthermore, from the aspect of financial benefits, bilateral loan have score of 41 and is more advantageous than the multilateral loan which score is 29.